2017
DOI: 10.1080/02705060.2017.1386595
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal feeding selectivity of brown trout Salmo trutta in five groundwater-dominated streams

Abstract: Availability and selection of macroinvertebrate prey is important to explain temporal and spatial variation in growth among stream salmonids. However, few studies contain information to identify such relationships. Our objectives were to quantify drift and benthic macroinvertebrate prey availability and selection by brown trout on a seasonal basis in five streams across three years in southeastern Minnesota. Few taxa were dominant in diets and the environment with considerable variability in drifting and benth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…While seasonal inputs of terrestrial invertebrates can have strong effects on trophic interactions in streams (Nakano et al 1999b, Nakano and Murakami 2001, Kawaguchi et al 2003, Baxter et al 2005), their relative effects can differ strongly across predator-prey interactions. For instance, seasonal diet shifts are ubiquitous among freshwater salmonids but are not widely observed in sculpin or salamanders (Wilhelm et al 1999, Li et al 2016, Cochran-Biederman and Vondracek 2017). Preston et al (2018a) also suggest that prey-specific sculpin feeding rates are relatively consistent across space and time in our study streams, especially compared to the more variable trout diets observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…While seasonal inputs of terrestrial invertebrates can have strong effects on trophic interactions in streams (Nakano et al 1999b, Nakano and Murakami 2001, Kawaguchi et al 2003, Baxter et al 2005), their relative effects can differ strongly across predator-prey interactions. For instance, seasonal diet shifts are ubiquitous among freshwater salmonids but are not widely observed in sculpin or salamanders (Wilhelm et al 1999, Li et al 2016, Cochran-Biederman and Vondracek 2017). Preston et al (2018a) also suggest that prey-specific sculpin feeding rates are relatively consistent across space and time in our study streams, especially compared to the more variable trout diets observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…riparian shading, aquatic vegetation and substratum composition), however, can influence prey selection patterns and diet composition (Newman & Waters, ; Holomuzki, ; Ryan & Kelly‐Quinn, ). Abundance and composition of aquatic invertebrates in the benthos and drift can vary significantly among streams and between seasons in south‐eastern Minnesota streams (Cochran‐Biederman, ) and can influence prey availability for S. trutta . In this case differences among streams in composition of aquatic invertebrate communities and S. trutta prey selection probably contributed to variation in S. trutta diet.…”
Section: Discussionmentioning
confidence: 99%
“…They also can detach their cases and graze algae or other organic materials from submerged surfaces under the proper conditions [33]. Because they often are very abundant, they can account for a significant proportion of the diet of trout [34,35], and at times are consumed preferentially by trout in numbers exceeding the larvae's proportional abundance in the macroinvertebrate community [35].…”
Section: Introductionmentioning
confidence: 99%